Special high-thermal-conductivity wear-resistant composite pipe as well as preparation method and application thereof
By using a specially made high-thermal and wear-resistant composite pipe composed of composite nano carbon tubes and composite alloys, the problems of unstable structure, poor thermal conductivity, low hardness and poor fire-resistant wear resistance of existing pipeline materials are solved, and high thermal conductivity, high hardness and good wear resistance are achieved, which is suitable for a variety of industrial applications.
Patent Information
- Application Number
- CN202510050753.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
AI Technical Summary
The existing pipeline materials have problems such as unstable structure, poor thermal conductivity, low hardness, and poor fire-resistant wear resistance, resulting in problems such as wear, corrosion, low heat transfer efficiency and easy damage under mechanical pressure.
A specially made high-thermal and wear-resistant composite tube composed of composite nanocarbon tubes and composite alloys enhances the structural stability and thermal conductivity of the pipeline through the combination of nanocarbon tubes and alloys, and improves hardness and wear resistance through the use of nickel-iron-titanium alloys.
It has achieved stable structure, high thermal conductivity, high hardness, fire resistance and wear resistance of the pipeline, and is suitable for high-demand application scenarios such as electricity, metallurgy, cement production, and chemical industries.
Smart Images

Figure BDA0005239884600000081 
Figure BDA0005239884600000082 
Figure BDA0005239884600000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of pipelines, and in particular to a special high-heat-conductivity and wear-resistant composite pipe and a preparation method and application thereof. Background Art
[0002] In many industrial fields, such as petrochemical, energy transmission, building water heating, etc., pipeline systems play a vital role. At present, pipeline materials have the following problems.
[0003] During the manufacturing process, pipes have defects caused by forging and stretching of steel, such as bubbles, interlayers, folds, uneven wall thickness, poor annealing, and grain size. Metal pipes are subject to wear and corrosion during use, and the pipe wall will gradually become thinner. When the pipe wall thickness is less than a certain value and is not treated accordingly, wear and corrosion pipe burst accidents will occur. When the actual wall temperature exceeds the applicable temperature of the metal, the mechanical properties and metallographic structure of the metal will change, the creep rate of the metal will accelerate, the strength will drop sharply, and finally the pipe will rupture. Many commonly used pipe materials, such as plastic pipes and ordinary carbon steel pipes, have relatively low thermal conductivity. In some application scenarios that require efficient heat transfer, such as heat exchange pipes in central heating systems and heat conduction pipes in chemical production, pipe materials with low thermal conductivity will lead to low heat transfer efficiency. Taking the central heating system as an example, when hot water flows in plastic pipes, due to the low thermal conductivity of plastics, heat is difficult to transfer quickly to the surrounding environment, making the indoor temperature rise slowly, which not only affects the heating effect, but also increases energy consumption. Nonferrous metal pipes such as copper pipes and aluminum pipes have good electrical conductivity, corrosion resistance and processing performance, but their hardness is relatively low. In some occasions that need to withstand certain mechanical pressure or friction, such as refrigerant delivery pipes in air conditioning refrigeration systems, scratches, deformation and even perforation are prone to occur. When the pipe rubs against the surrounding fixed parts or other pipes, the surface is easily worn due to insufficient hardness, which affects the sealing and service life of the pipe, may cause refrigerant leakage, and reduce the efficiency of the refrigeration system. When the temperature of carbon steel pipes exceeds a certain level, their strength and hardness will decrease significantly, and their anti-oxidation performance will deteriorate. In the high-temperature flue gas delivery pipes of steel smelters, carbon steel pipes are in a high-temperature oxidation and corrosion environment for a long time, and iron oxide scale will quickly form on the surface, which will continue to peel off, resulting in thinning of the pipe wall thickness, and eventually rupture, affecting the continuity and safety of production. When many pipes are transporting solid particles or high-viscosity fluids, the inner wall of the pipe will be severely worn due to insufficient wear resistance. In the slurry pipeline of the mine, the high-speed flow of ore particles and slurry will constantly wash the inner wall of the pipeline. Ordinary metal or plastic pipelines will soon be worn and pitted, resulting in reduced pipeline transportation efficiency and increased leakage risk. As the wear increases, the pipeline may need to be replaced frequently, increasing production costs and maintenance workload.
[0004] In view of the problems existing in the prior art, this application aims to solve the problems of unstable pipeline structure, poor thermal conductivity, low hardness, poor fire resistance and wear resistance. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a special high thermal conductivity and wear-resistant composite pipe and its preparation method and application, so as to solve the problems of unstable structure, poor thermal conductivity, low hardness, poor fire resistance and wear resistance of existing pipelines.
[0006] The technical solution of the present invention:
[0007] The invention discloses a special high thermal conductivity wear-resistant composite tube, characterized in that the special high thermal conductivity wear-resistant composite tube is composed of composite nano-carbon tubes and composite alloys, and the composite alloys are in the inner layer or outer layer of the composite nano-carbon tubes.
[0008] Furthermore, the raw materials for preparing the composite nano-carbon tubes include: nano-carbon materials, metal composite materials, polymer compounds, and strengthening additives.
[0009] The preparation of the composite nano-carbon tubes comprises the following steps:
[0010] (1) adding nano-carbon materials into a reaction kettle, and then adding an acidic mixed solution to pretreat the nano-carbon materials;
[0011] (2) adding the nano-carbon material, metal composite material and strengthening agent pretreated in step (1) into chlorosulfonic acid, controlling the temperature at 0-10° C. and stirring for 1-3 hours to form a uniform composite carbon nanotube dispersion;
[0012] (3) adding the polymer compound to the composite carbon nanotube dispersion prepared in step (2), stirring and mixing to form a uniform spinning solution;
[0013] (4) pouring the prepared spinning solution into a liquid storage tank of a spinning device, and extruding it into a coagulation bath through a spinneret for wet spinning;
[0014] (5) subjecting the fiber obtained by wet spinning in step (4) to high-temperature carbonization treatment under the protection of an inert atmosphere to obtain carbon tube fiber;
[0015] (6) The carbon tube fiber after high-temperature carbonization treatment in step (5) is heated and kept warm for a period of time, and then placed in a cylindrical mold containing a core rod for hot pressing to obtain a hollow composite nano-carbon tube;
[0016] (7) The carbon tube fiber subjected to high temperature carbonization treatment in step (5) is heated and kept at a high temperature for a period of time, and then placed in a cylindrical mold for hot pressing to obtain a solid composite nano-carbon tube.
[0017] The preparation of the polymer compound comprises the following steps:
[0018] S1: Add 2-hydroxybenzaldehyde and dimethylformamide into a three-necked flask, then add aspartic acid and tetrabutyl titanate, and stir evenly;
[0019] S2: raising the temperature of step S1 to 100-120°C for 10-16 hours;
[0020] S3: After the reaction in step S2 is completed, the reaction solution is cooled to room temperature and then poured into cold water to precipitate the polymer. The polymer precipitate obtained is filtered, washed with deionized water, and then dried in a vacuum drying oven to constant weight at a drying temperature of 50-60°C and a drying time of 12-24 hours to obtain a polymer compound.
[0021] The preparation of the metal composite material comprises the following steps:
[0022] S1: Add various metal powders into a ball mill according to a certain proportion, add an appropriate amount of ethanol to mix them by ball milling, and ball mill for 0.5-1 hour to obtain a uniformly mixed metal composite powder, dry the metal composite powder in a vacuum drying oven at a drying temperature of 40-60°C, remove the ethanol and set aside;
[0023] S2: mixing the metal composite powder dried in step S1 with phenolic resin in a certain ratio, and kneading them in a mixer to obtain a kneaded mixture;
[0024] S3: placing the kneaded mixture prepared in step S2 into a mold, and performing hot pressing molding on a hot press, the hot pressing temperature is 180-200° C., the pressure is 20-30 MPa, and the holding time is 1-2 hours;
[0025] S4: Sintering the sample formed by hot pressing in step S3 in a nitrogen atmosphere at a sintering temperature of 1600-1800° C. for a heat preservation time of 2-3 hours to obtain a metal composite material.
[0026] Furthermore, the metal powder in step S1 is a mixture of one or more of nickel powder, chromium powder, titanium powder, silver powder, tungsten powder, molybdenum powder and manganese powder.
[0027] Furthermore, the strengthening aid is a mixture of one or more of silicon dioxide, calcium oxide and calcium sulfate.
[0028] The metal used to prepare the composite alloy is a combination of two or more of nickel powder, iron powder, titanium powder, chromium powder, silver powder, tin powder, molybdenum powder, zinc powder and manganese powder.
[0029] The preparation method of the composite alloy comprises the following steps:
[0030] S1: putting the metals for preparing the composite alloy into a stainless steel ball mill according to proportion, and ball milling for a period of time;
[0031] S2: putting the metals mixed evenly in step S1 into an electric arc furnace for smelting while mechanically stirring;
[0032] S3: Casting the alloy melted in step S2 into a plate, and then processing it by turning and grinding for standby use to obtain a composite alloy.
[0033] Furthermore, the metals used to prepare the composite alloy are nickel powder, iron powder and titanium powder, and the mass ratio of nickel powder, iron powder and titanium powder is 1-2:1-1.5:1.
[0034] Furthermore, in step S1, the speed of the stainless steel ball milling is 1000-1200 rpm, and the ball milling time is 50-60 hours.
[0035] Furthermore, the smelting temperature in step S2 is 1000-1500° C., and the mechanical stirring is performed for 1-2 hours.
[0036] The present invention also provides a method for preparing a special high thermal conductivity and wear-resistant composite pipe, comprising the following steps:
[0037] (1) Using a mold with a mandrel structure, the composite carbon nanotube is sleeved on the mandrel of the mold, and then the molten composite alloy is injected into the gap between the outside of the mandrel and the inside of the composite carbon nanotube by a pressure of 1-10 MPa;
[0038] (2) After the alloy is injected, the mold temperature is kept stable to allow the alloy to slowly solidify inside the carbon nanotubes at a cooling rate of 1-10°C / min. After the alloy is completely solidified, the composite tube is removed from the mold to obtain a special high thermal conductivity and wear-resistant composite tube with an inner layer of the composite alloy.
[0039] The present invention also provides a method for preparing a special high thermal conductivity and wear-resistant composite pipe, comprising the following steps:
[0040] (1) Using a mold with a mandrel structure, the composite carbon nanotubes are sleeved on the mandrel of the mold, and then the molten composite alloy is injected into the outside of the composite carbon nanotubes and the inside of the mold at a pressure of 1-10 MPa;
[0041] (2) After the alloy is injected, the mold temperature is kept stable to allow the alloy to slowly solidify outside the composite nano-carbon tubes at a cooling rate of 1-10°C / min. After the alloy is completely solidified, the composite tube is removed from the mold to obtain a special high thermal conductivity and wear-resistant composite tube with a composite alloy outer layer.
[0042] The invention discloses an application of a special high thermal conductivity wear-resistant composite pipe, wherein the special high thermal conductivity wear-resistant composite pipe is applied to the electric power, metallurgy, cement production and chemical industries.
[0043] The invention discloses a special high thermal conductivity and wear-resistant composite pipe, which uses a composite alloy and a composite nano carbon tube combination to further enhance the structural stability of the carbon tube, and uses a nickel-iron-titanium alloy. The low density of titanium reduces the overall density of the nickel-iron-titanium alloy, thereby achieving a lightweight structure while maintaining a relatively high strength. The good thermal conductivity of titanium and the comprehensive influence of elements such as nickel and iron on the thermal conductivity of the alloy make the nickel-iron-titanium alloy have a relatively high thermal conductivity. Both nickel and titanium can significantly improve the hardness of the alloy, and coupled with the strengthening effect of the iron element, the nickel-iron-titanium alloy has a very high hardness. The high temperature resistance of nickel and titanium and the high hardness and high strength of the alloy as a whole give the nickel-iron-titanium alloy good fire resistance and wear resistance, so that the prepared special high thermal conductivity and wear-resistant composite pipe has a light structure, high thermal conductivity, high hardness, fire resistance and wear resistance, and has good application prospects in the electric power, metallurgy, cement production and chemical industries.
[0044] Beneficial effects:
[0045] The present invention provides a special high thermal conductivity and wear-resistant composite pipe, which has a stable structure, a light structure, high thermal conductivity, high hardness, fire resistance and wear resistance, and has good application prospects in the electric power, metallurgy, cement production and chemical industries. DETAILED DESCRIPTION
[0046] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0047] Unless otherwise specified, the chemical reagents used in the present invention are all commercially available analytically pure. The phenolic resin model is BMJ-92, purchased from Ruibo Chemical Co., Ltd.
[0048] Preparation of metal composite materials:
[0049] S1: 1 kg of nickel powder, 0.5 kg of chromium powder and 0.5 kg of titanium powder were added into a ball mill, and 5 L of ethanol was added for ball milling and mixing. The mixture was ball milled for 0.5 hours to obtain a uniformly mixed metal composite powder. The metal composite powder was dried in a vacuum drying oven at a drying temperature of 50°C, and the ethanol was removed for later use;
[0050] S2: adding 0.4 kg of phenolic resin to the metal composite powder dried in step S1 according to a certain ratio, and mixing in a mixer to obtain a mixed mixture;
[0051] S3: placing the kneaded mixture prepared in step S2 into a mold, and performing hot pressing molding on a hot press, the hot pressing temperature is 180° C., the pressure is 25 MPa, and the holding time is 2 hours;
[0052] S4: Sintering the sample formed by hot pressing in step S3 in a nitrogen atmosphere at a sintering temperature of 1800° C. for a heat preservation time of 2 hours to obtain a metal composite material.
[0053] Preparation of polymer compounds:
[0054] S1: Add 1 kg of 2-hydroxybenzaldehyde and 1 L of dimethylformamide into a three-necked flask, then add 1 kg of aspartic acid and 0.04 kg of tetrabutyl titanate, and stir evenly;
[0055] S2: Heat the reaction in step S1 to 120°C for 12 hours;
[0056] S3: After the reaction in step S2 is completed, the reaction solution is cooled to room temperature and then poured into cold water to precipitate the polymer. The polymer precipitate obtained is filtered, washed with deionized water, and then dried in a vacuum drying oven to constant weight at a drying temperature of 50° C. for 24 hours to obtain a polymer compound.
[0057] Preparation of composite carbon nanotubes:
[0058] (1) Add 4 kg of carbon nanotubes into a reactor, and then add an acidic mixed solution (the mass ratio of concentrated sulfuric acid to concentrated nitric acid is 1:1) with a mass of 5 times the mass of the carbon nanotubes to pretreat the carbon nanomaterials;
[0059] (2) adding the carbon nanotubes pretreated in step (1), 2 kg of the metal composite material, 0.1 kg of silicon dioxide, 0.02 kg of calcium oxide, and 0.01 kg of calcium sulfate to chlorosulfonic acid 10 times the mass of the carbon nanotubes and the metal composite material, controlling the temperature at 0° C. and stirring for 2 hours to form a uniform composite carbon nanotube dispersion;
[0060] (3) adding the polymer compound to the composite carbon nanotube dispersion prepared in step (2), stirring and mixing to form a uniform spinning solution, the stirring speed is 1000 rpm, and the stirring time is 5 hours;
[0061] (4) pouring the prepared spinning solution into a liquid storage tank of a spinning device, and extruding it through a spinneret into a coagulation bath for wet spinning, wherein the coagulation bath is an aqueous solution of water and calcium chloride (the mass ratio of water to calcium chloride is 10:1), the temperature is 20° C., the extrusion pressure is 0.25 MPa, and the drawing speed is 2 m / min;
[0062] (5) subjecting the fiber obtained by wet spinning in step (4) to high-temperature carbonization treatment under nitrogen protection, with a heating rate of 10° C. / min, a carbonization temperature of 1000° C., and a holding time of 2 hours to obtain carbon fiber tubes;
[0063] (6) The carbon tube fiber after high-temperature carbonization treatment in step (5) is then heated to 2500° C., kept warm for 1 hour, and then placed in a mold with an outer diameter of 23 mm, an inner diameter of 21 mm, and a length of 110 mm for hot pressing to obtain a hollow composite nano-carbon tube A;
[0064] (7) The carbon tube fiber treated with high temperature carbonization in step (5) is heated to 2500° C., kept at this temperature for 1 hour, and then placed in a mold with an outer diameter of 22 mm, an inner diameter of 20 mm, and a length of 110 mm for hot pressing to obtain a hollow composite nano-carbon tube B.
[0065] Preparation of composite alloy A:
[0066] S1: 2 kg nickel powder, 1 kg iron powder and 1 kg titanium powder were put into a stainless steel ball mill in proportion. The speed of the stainless steel ball mill was 1000 rpm and the ball milling time was 50 hours.
[0067] S2: putting the metal mixed evenly in step S1 into an electric arc furnace for smelting while mechanically stirring at a smelting temperature of 1200° C. for 2 hours;
[0068] S3: The alloy melted in step S2 is cast into a plate, and then processed by turning and grinding for standby use to obtain a composite alloy A.
[0069] Preparation of composite alloy B:
[0070] S1: 1 kg nickel powder, 1.5 kg tin powder and 1 kg zinc powder were put into a stainless steel ball mill in proportion. The speed of the stainless steel ball mill was 1000 rpm and the ball milling time was 50 hours.
[0071] S2: putting the metal mixed evenly in step S1 into an electric arc furnace for smelting while mechanically stirring at a smelting temperature of 1200° C. for 2 hours;
[0072] S3: The alloy melted in step S2 is cast into a plate, and then processed by turning and grinding for standby use to obtain a composite alloy B.
[0073] Preparation of composite alloy C:
[0074] S1: 0.5 kg nickel powder, 2 kg iron powder and 1 kg titanium powder were put into a stainless steel ball mill in proportion. The speed of the stainless steel ball mill was 1000 rpm and the ball milling time was 50 hours.
[0075] S2: putting the metal mixed evenly in step S1 into an electric arc furnace for smelting while mechanically stirring at a smelting temperature of 1200° C. for 2 hours;
[0076] S3: The alloy melted in step S2 is cast into a plate, and then processed by turning and grinding for standby use to obtain a composite alloy C.
[0077] Embodiment 1:
[0078] Preparation of special high thermal conductivity and wear-resistant composite pipe:
[0079] (1) A cylindrical mold having a core shaft with a diameter of 20 mm and a length of 110 mm, an inner diameter of 23 mm and an outer diameter of 25 mm is used, and a hollow composite nano-carbon tube A with an outer diameter of 23 mm, an inner diameter of 21 mm and a length of 110 mm is sleeved on the outside of the core shaft of the mold, and then the molten composite alloy A is injected at a pressure of 2 MPa to fill the gap between the outside of the core shaft and the inside of the composite nano-carbon tube A. When the composite alloy A is injected, the temperature of the mold is 1100°C;
[0080] (2) After the composite alloy A is injected, the mold is maintained at 1100°C, and then the composite alloy A is slowly solidified inside the carbon nanotubes at a cooling rate of 5°C / min. After the alloy is completely solidified, the composite tube is removed from the mold to obtain a special high thermal conductivity and wear-resistant composite tube with an inner layer of the composite alloy.
[0081] Embodiment 2:
[0082] (1) A mold having a cylindrical structure with a core shaft having a diameter of 20 mm and a length of 110 mm, an inner diameter of 23 mm and an outer diameter of 25 mm is used, a hollow composite nano-carbon tube B having an outer diameter of 22 mm, an inner diameter of 20 mm and a length of 110 mm is sleeved in the core shaft of the mold, and then the molten composite alloy A is injected at a pressure of 2 MPa to fill the gap between the outside of the composite nano-carbon tube B and the inside of the cylindrical structure having an inner diameter of 23 mm and an outer diameter of 25 mm. When the composite alloy A is injected, the temperature of the mold is 1100°C;
[0083] (2) After the composite alloy A is injected, the mold is maintained at 1100°C, and then the composite alloy A is slowly solidified outside the composite nano-carbon tube B at a cooling rate of 5°C / min. After the alloy is completely solidified, the composite tube is removed from the mold to obtain a special high thermal conductivity and wear-resistant composite tube with an outer layer of the composite alloy.
[0084] Embodiment 3:
[0085] The difference between the special high thermal conductivity and wear-resistant composite pipe prepared in this preparation example and Example 1 is that the composite alloy A is replaced by composite alloy B in step (1).
[0086] Embodiment 4:
[0087] The difference between the special high thermal conductivity and wear-resistant composite pipe prepared in this preparation example and Example 1 is that the composite alloy A in step (1) is replaced by composite alloy C.
[0088] Comparative Example 1:
[0089] The difference between the special high thermal conductivity and wear-resistant composite tube prepared in this preparation example and in Example 1 is that the composite nano-carbon tubes in step (1) are replaced by nano-carbon tubes.
[0090] Comparative Example 2:
[0091] The difference between the special high thermal conductivity and wear-resistant composite pipe prepared in this preparation example and Example 1 is that the composite alloy A in step (3) is replaced by titanium alloy.
[0092] Comparative Example 3:
[0093] The difference between the special high thermal conductivity and wear-resistant composite pipe prepared in this preparation example and in Example 1 is that in step (3), the composite alloy A is replaced by an iron alloy.
[0094] The special high thermal conductivity and wear-resistant composite pipes prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to the following performance tests:
[0095] 1. Thermal conductivity test:
[0096] According to the standard GB / T 8722-2019 "Determination method of thermal conductivity of carbon materials", the thermal conductivity of the specially made high thermal conductivity and wear-resistant composite pipes prepared in Examples 1-4 and Comparative Examples 1-2 was tested.
[0097] 2. Hardness test:
[0098] According to the standard GB / T 39535-2020 "High-temperature composite metal high-temperature long-lasting stress relaxation test method", the hardness test of the specially made high thermal conductivity and wear-resistant composite pipes prepared in Examples 1-4 and Comparative Examples 1-3 was carried out.
[0099] 3. Thermal expansion coefficient test:
[0100] According to the standard JB / T 8133.18-2017 "Test methods for physical and chemical properties of electric carbon products Part 18: Linear expansion coefficient", the carbon tube samples with a size of φ20 mm×160 mm prepared from the specially made high thermal conductivity and wear-resistant composite tubes prepared in Examples 1-4 and Comparative Examples 1-3 were tested for thermal expansion coefficient.
[0101] 4. Resistivity test:
[0102] According to the standard GB / T 24525-2009 "Determination of resistivity of carbon materials" 158, the resistivity of the specially made high thermal conductivity and wear-resistant composite pipes prepared in Examples 1-4 and Comparative Examples 1-3 was tested.
[0103] 5. Flexural strength test:
[0104] According to the standard GB / T 3074.1-2021 "Determination method of flexural strength of carbon materials", the flexural strength of the specially made high thermal conductivity and wear-resistant composite pipes prepared in Examples 1-4 and Comparative Examples 1-3 was tested.
[0105] 6. Bulk density test:
[0106] According to the standard GB / T 24528-2009 “Determination method of bulk density of carbon materials”, bulk density tests were performed on the specially made high thermal conductivity and wear-resistant composite pipes prepared in Examples 1-4 and Comparative Examples 1-3.
[0107] Table 1: Test results
[0108]
[0109] Table 2: Test results
[0110]
[0111]
[0112] From the above data, it can be seen that the specially prepared high thermal conductivity and wear-resistant composite tubes in Examples 1-3 have a light structure, high thermal conductivity, high hardness, fire resistance, and wear resistance, and will not produce excessive deformation due to thermal expansion and contraction; from the comparison between Example 4 and Example 2, it can be seen that adjusting the mass ratio of nickel powder, iron powder and titanium powder in the nickel-iron-titanium alloy will reduce the hardness of the prepared specially prepared high thermal conductivity and wear-resistant composite tube, reduce the linear expansion coefficient, reduce the flexural strength, and the performance is lower than the expected effect; from the comparison between Comparative Example 1 and Example 2, it can be seen that replacing the prepared composite nano-carbon tubes with single nano-carbon tubes will cause the thermal conductivity of the prepared specially prepared high thermal conductivity and wear-resistant composite tube to deteriorate, The hardness is reduced, the linear expansion coefficient becomes smaller, the flexural strength becomes lower, and the expected effect cannot be achieved; from the comparison between Comparative Example 2 and Example 2, it can be seen that replacing the composite alloy A with a single titanium alloy will cause the thermal conductivity of the prepared special high thermal conductivity and wear-resistant composite pipe to deteriorate, the hardness is reduced, the linear expansion coefficient becomes smaller, the resistivity becomes smaller, and the flexural strength becomes lower, and the expected effect cannot be achieved; from the comparison between Comparative Example 3 and Example 2, it can be seen that replacing the composite alloy A with an iron alloy will cause the thermal conductivity of the prepared special high thermal conductivity and wear-resistant composite pipe to deteriorate, the hardness is reduced, the linear expansion coefficient becomes smaller, the resistivity becomes smaller, and the flexural strength becomes lower, and the expected effect cannot be achieved.
[0113] The present invention can also have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. A special high thermal conductivity and wear-resistant composite pipe, characterized in that: The specially made high-heat-conductivity and wear-resistant composite tube is composed of composite nano-carbon tubes and composite alloys, and the composite alloy is in the inner layer or outer layer of the composite nano-carbon tubes.
2. The specially made high thermal conductivity and wear-resistant composite pipe according to claim 1, characterized in that: The raw materials for preparing the composite nano carbon tubes include: nano carbon materials, metal composite materials, high polymer compounds and strengthening additives.
3. The specially made high thermal conductivity and wear-resistant composite pipe according to claim 1 is characterized in that: The metal used to prepare the composite alloy is a combination of two or more of nickel powder, iron powder, titanium powder, chromium powder, silver powder, tin powder, molybdenum powder, zinc powder and manganese powder.
4. The specially made high thermal conductivity and wear-resistant composite pipe according to claim 1, characterized in that: The preparation method of the composite alloy comprises the following steps: S1: putting the metals for preparing the composite alloy into a stainless steel ball mill according to proportion, and ball milling for a period of time; S2: putting the metals mixed evenly in step S1 into an electric arc furnace for smelting while mechanically stirring; S3: Casting the alloy melted in step S2 into a plate, and then processing it by turning and grinding for standby use to obtain a composite alloy.
5. The specially made high thermal conductivity and wear-resistant composite pipe according to claim 4 is characterized in that: The metals used to prepare the composite alloy are nickel powder, iron powder and titanium powder, and the mass ratio of the nickel powder, the iron powder and the titanium powder is 1-2:1-1.5:
1.
6. The specially made high thermal conductivity and wear-resistant composite pipe according to claim 4, characterized in that: The speed of the stainless steel ball milling in step S1 is 1000-1200 rpm, and the ball milling time is 50-60 hours.
7. The specially made high thermal conductivity and wear-resistant composite pipe according to claim 4, characterized in that: The smelting temperature in step S2 is 1000-1500° C., and the mechanical stirring is performed for 1-2 hours.
8. The method for preparing the special high thermal conductivity and wear-resistant composite pipe according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Using a mold with a mandrel structure, the composite carbon nanotube is sleeved on the mandrel of the mold, and then the molten composite alloy is injected into the gap between the outside of the mandrel and the inside of the composite carbon nanotube by a pressure of 1-10 MPa; (2) After the alloy is injected, the mold temperature is kept stable to allow the alloy to slowly solidify inside the carbon nanotubes at a cooling rate of 1-10°C / min. After the alloy is completely solidified, the composite tube is removed from the mold to obtain a special high thermal conductivity and wear-resistant composite tube with an inner layer of the composite alloy.
9. The method for preparing the special high thermal conductivity and wear-resistant composite pipe according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Using a mold with a mandrel structure, the composite carbon nanotubes are sleeved on the mandrel of the mold, and then the molten composite alloy is injected into the outside of the composite carbon nanotubes and the inside of the mold at a pressure of 1-10 MPa; (2) After the alloy is injected, the mold temperature is kept stable to allow the alloy to slowly solidify outside the composite nano-carbon tubes at a cooling rate of 1-10°C / min. After the alloy is completely solidified, the composite tube is removed from the mold to obtain a special high thermal conductivity and wear-resistant composite tube with a composite alloy outer layer.
10. The application of the specially made high thermal conductivity and wear-resistant composite pipe according to any one of claims 1 to 7, characterized in that: The specially made high thermal conductivity and wear-resistant composite pipe is used in the electric power, metallurgy, cement production and chemical industries.